Should the Indonesia's Audit Board (BPK RI) Supervise the General Election Campaign Funds? - Dirgantara, Arsih Ardivya Putra; Al-Fatih, Sholahuddin (Audito Comparative Law Journal (ACLJ), 2026)
This manuscript examines the phenomenon of money politics in the General Election (Pemilu) contestation in Indonesia. Money politics is not only a technical problem in elections but has become a clinical pathology as a form of co-optation of people's sovereignty by capital owners and political elites. Thus, money politics negates the meaning of elections as a means of democracy instead turning it into an arena for the circulation of power by a handful of groups without substantial ideas and programs. Seeing this phenomenon, this manuscript uses a socio-legal research method to coherently see between the Law normatively and the sociological facts of the occurrence of money politics in society. With a comparative causal approach and a normative approach, the manuscript is expected to provide a comprehensive explanation and specific findings to recommend regulatory updates and real impacts on the academic world, especially law and society. A brief conclusion in the manuscript shows that money politics is one of the structural problems in society and the lack of effectiveness in regulations, especially legal rules on elections, proves that gradual changes in election regulations are needed from the previous one involving 3 (three) institutions; The KPU, Bawaslu, and DKPP as well as the independent KAP institution for audit work of a compliance nature in regional elections, have led to the involvement of the BPK RI as an examination institution to expand its authority to audit work of an investigative and evaluative nature.